PERANCANGAN SISTEM KONTROL SUHU DAN KELEMBAPAN UDARA PADA KUBIKEL 20KV BERBASIS INTERNET OF THINGS (IOT) - Moch. Gembong Abi Rahman; Suwasti Broto (MAESTRO, 2020)
The problem that often occurs in cubicles today is the corona, a phenomenon that occurs when the air around the conductor or conductor is ionized. This is what accelerates the occurrence of the corona. The design of the temperature and humidity control system is made using the Wemos D1 Mini microcontroller, the DHT11 sensor as a temperature and humidity reader sensor, this tool also uses a relay as an automatic switch to turn on and off the fan and also a dehumidifier and installed NodeMCU Esp8266 to send results to smartphones. The way the temperature and humidity control system works using the DHT11 sensor, the sensor senses the temperature and humidity objects in the cubicle, then the data obtained will be processed by the Wemos D1 Mini microcontroller in serial communication. Then the received data will be processed according to the set point, where the temperature is set at 35ºC and the humidity is set at 50% RH. So that if the temperature and humidity are more than the set point value, the relay will work to activate the dehumidifier and fan until the temperature and humidity reach the specified values then it will turn off again. And the data that has been read will be displayed on the LCD / smartphone and stored in the database. From the results of taking temperature and humidity data at substations SP13, KJ274 and KJ365, the results were obtained to test the prototype tool. It takes 8 minutes for the humidity to reach 79% of the initial value of 30% and 13 minutes for the temperature to reach 49ºC from the initial temperature of 26ºC. In the test, the prototype tool can control temperature and humidity to the bottom of the set point and keep it below the set point, so that the occurrence of coronas caused by high humidity can be minimized.